MODEL INTERPOLASI GEOSTATISTIK LOGAM BERAT DAN BIOTA DI PERAIRAN MUARA SUNGAI KUIN - Abdur Rahman (Universitas Lambung Mangkurat, 2012)
This study aimed to model the spatial content of heavy metals in water bodies and biota in the waters of the River Estuary Kuin. Data analysis methods are used to determine water quality status with spatial interpolation models Semivariogram (kriging) and Inverse Distance weighting (IDW) is integrated with Geographic Information System (GIS). Based on calculations using the Ordinary Kriging method with Semivariogram/covariance modeling to model the heavy metals in water bodies Average Standard Error values average of 0.01641 (RMS = 0.01430) at the station Kuin River Estuary. Results of calculations using the Inverse Distance weighting method (IDW) for models of heavy metals in biota obtained Root Mean Square value (RMS-error) average of 0.29787 on Kuin River Estuary, and the mean value of the average station of 0.0138.